2009
DOI: 10.3174/ajnr.a1824
|View full text |Cite
|
Sign up to set email alerts
|

Value of Coronal Reformations in the CT Evaluation of Acute Head Trauma

Abstract: Coronal reformations improve the detection of ICH over axial images alone, especially for lesions that lie in the axial plane immediately adjacent to bony surfaces. The use of coronal reformations should be considered in the routine interpretation of head CT examinations performed for the evaluation of head trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 11 publications
(11 reference statements)
0
24
0
5
Order By: Relevance
“…A few studies have assessed the added value of three-dimensional (3D) reformations versus transverse plane views in the evaluation of cranial CT examinations (5,6). To our knowledge, however, no reported study has evaluated the effect of 3D reformatted images on radiology residents' performance.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have assessed the added value of three-dimensional (3D) reformations versus transverse plane views in the evaluation of cranial CT examinations (5,6). To our knowledge, however, no reported study has evaluated the effect of 3D reformatted images on radiology residents' performance.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings indicate that small collections can be both overlooked and undetectable with CT imaging, even when using reformations, which has been shown to improve detection in living patients. 4 It has been previously demonstrated that a limitation of CT virtual autopsy is the possibility of missing very small collections of blood. Yen et al 5 evaluated postmorten brains with traumatic injury and found that CT had a sensitivity of 73% for the detection of subdural hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Evaluation of coronal images in HL is important for disease bulk positioned obliquely in the mediastinum or for conglomerate lymph node mass extending along the cranio-caudal axis, such as involvement of contiguous cervical, supraclavicular, and infraclavicular lymph nodes. We found additional patients (approx.…”
Section: Discussionmentioning
confidence: 99%